IPO MARKET: TRANSFORMATION OF SAVINGS INTO INVESTMENTS - Mergenbaeva A. T.; Nurasheva K. K; Kulanova D. A.; Abdikerimova G. I.; Abishova A. U.; Alibek A. M. (Scientific Journal of Pedagogy and Economics, 2019)
The intensity of IPO implementation, their effectiveness and success, as well as the activity in IPO markets are among the factors allowing assessing the state of national and global economies, as well as to determine investors’ sentiment and predict their behavior. Participants of IPO process should take into account the manifestation of global, regional and national regularities and trends in the market of initial public offers. The global IPO market is influenced by various factors, including macroeconomic, political and geopolitical ones. One of the fundamental goals of IPO transaction realization is maximization of the attracted capital, while the key participants of the placement face a conflict of interests. Qualitative execution of technical preparation for holding an IPO does not guarantee a successful, efficient and profitable placement. A particular impact on the efficiency of placements is provided by the choice of a good time to conduct an IPO, which largely depends on the business cycle of the market. At present, there is a need to diversify Kazakhstan economy and equalize the imbalance caused by high raw product dependence. Economic reforms and development of new high-tech sectors increase the need of companies in investments. The development of Kazakhstan IPO market is of strategic importance for stimulating economic growth and increasing the level of liquidity and capital intensity of the national market of securities. Despite the fact that in Kazakhstan, the current practice of IPO placement has a relatively short history, it can be noted that a number of successful placements has already been made, and the market of initial public offering has been formed, although it has not yet reached a level comparable with developed economies. The dynamic development of the foreign market of Kazakhstan IPOs and public resonance of the conducted placements led to the fact that Kazakhstan companies are paying increasing attention to this method of attracting capital.